DOKUMENTASI KONDISI KEHIDUPAN WILAYAH KECAMATAN BUNGUS MELALUI FOTO DAN VIDEO - Yuni Handayani Gusmira; Dessy Abdullah; Deska Ismaya; Nur Fadilah Assuhriyah; Nazwa Aliefia Adzani; Salsabila Fauzia (Yayasan Nusantara Hasana Berdikari, 2023)
The city of Padang is one of the areas in Indonesia which is famous for its natural beauty, one of the famous tourist attractions in the city of Padang is Bungus. Documenting the life of the people of Teluk Kabung Village, Bungus District through photos and videos is one way to promote the beauty of nature in the city of Padang. Bungus District is one of the areas in the coastal area. This sub-district is a coastal sub-district in the southern region of Padang City with an area of ​​100.78 km2 and a population of 23,400 people. Bungus also has maritime wealth which is used as a tourist attraction in the form of beaches and islands. Bungus Bay has natural resources that have the potential to be developed as a tourist area because it has a sloping beach and white sand, stretching from north to south with a very strategic position close to the provincial capital. This bay is suitable for various recreational beach tourism activities. This service is carried out to find out how the people in the Bungus City area live every day. This dedication also emphasizes things in the form of activities, circumstances, social phenomena whose meaning behind these events can be taken as lessons for the development of theoretical concepts. The method used is a qualitative method where this method really requires the presence of the servant in the field and must be carried out optimally because it can assist the servant in obtaining the desired data without manipulating the data. The results of this activity found that most of the people in the Bungus area work as fishermen. Apart from being fishermen, many people work as farmers because the paddy fields in this area are quite extensive. The economy of the people of this area is on average middle to lower. By carrying out this event, it is hoped that the people of the Bungus area can maintain and improve the economy and health.